Effect of different doses of intravenous dexmedetomidine as an adjunct to the serratus anterior plane block in patients undergoing modified radical mastectomy: a randomized controlled trial - Lvdan Huang; Shishi Zhao; Weijuan Zhu; Xiaona Zhu; Linmin Pan; Quanguang Wang; Kejian Shi (Annals of Medicine)
Objective This study aimed to observe the effect of different doses of intravenous dexmedetomidine as an adjunct to the serratus anterior plane block (SAPB) on postoperative analgesia in patients undergoing modified radical mastectomy.Patients and Methods Eighty-five patients scheduled for modified radical mastectomy were recruited and randomly divided into R, RD 0.5, and RD 1.0 groups. All three groups underwent preoperative SAPB. During surgery, intravenous infusion of saline (50 mL) or saline with dexmedetomidine (50 mL) was administered (no dexmedetomidine in Group R, 0.5 μg/kg dexmedetomidine in Group RD 0.5, and 1.0 μg/kg dexmedetomidine in Group RD 1.0). The primary outcome of the trial was the area under the curve (AUC) of the Numerical Rating Scale (NRS) pain intensity scores upon movement within 24 h. Secondary outcomes included the AUC of the NRS pain intensity scores at rest within 24 h, postoperative oral morphine equivalents (OME), Quality of Recovery-15 (QoR-15), and incidence of adverse events.Results At rest and upon movement, the 24-h AUC of NRS pain scores in the RD 1.0 group was significantly lower than that in the R group (p = 0.003 and p < 0.001). The postoperative OME in the RD 1.0 group significantly decreased than that in the R group (p = 0.012). The RD 0.5 group and the R group showed no significant differences in the 24-h AUC of NRS pain scores and postoperative OME (all p > 0.05). The postoperative QoR-15 in the RD 0.5 and RD 1.0 groups were significantly higher than those in the R group (both p < 0.001). A significant difference was observed in the sedation status 1 h postoperatively between the RD 1.0 and R groups (p = 0.009).Conclusion Administration of 1.0 µg/kg intravenous dexmedetomidine as an adjunct to SAPB significantly reduces the postoperative pain intensity in patients undergoing modified radical mastectomy and decreases the postoperative consumption of analgesics.Trial registration The trial was registered at the Chinese Clinical Trial Registry (ChiCTR2300071444, date of registration: May 16, 2023); pre-results